MATERNAL OBESITY INCREASES RISK OF PREECLAMPSIA AND DIABETES MELLITUS - Naura Ega Kahayani; Hermanto Tri Joewono; Rio Wironegoro (Majalah Biomorfologi, 2021)
Background: Obesity in pregnant women has been linked to negative outcomes for both the mother and the fetus. Gestational diabetes, preeclampsia, and postpartum haemorrhage are all threats for mothers during pregnancy. These may also affect labor outcomes because fat accumulation in the pelvis makes obese pregnant women more likely to have a caesarean section. Objective: To analyze the outcome of maternal obesity in pregnancy in 2017. Materials and Methods: This was an analytic cross-sectional, observational study in pregnant women with obesity in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, within the period of January 1st – December 31st 2017 using medical records. Sample size was determined using cross-sectional sample size calculation with the result of n=162. After receiving approval of ethical clearance, medical records were collected and analyzed. The statistical analysis was done using chi-square test. Results: From a total of 162 subjects, most of the patients were 21-34 y/o (56.8%), under graduate (90.7%) and 58% of the subjects worked. Proportion of grade I, II and III were 60.5%, 22.2%, and 17.3%, and 67% suffered from complications such as PE, DM, PE with DM with percentages as follows: 56.2%, 4.9%, and 6.2%. Neonatal complications were preterm 42.6%, macrosomia 4.3%, stillbirth 4.9%, and low Apgar score 48.1%. No association was identified between maternal age and complications in grade I (p=0.764) and grade III (p=0.716). Obesity grades I and III had correlation with complications (p=0.035). Conclusion: No significant association was found between age and complications in grade III obesity, while there was significant correlation between obesity levels (grade I and grade III) and complications.